Stable expression of silencing‐suppressor protein enhances the performance and longevity of an engineered metabolic pathway. Issue 6 (2nd December 2015) - Naim, Fatima; Shrestha, Pushkar; Singh, Surinder P.; Waterhouse, Peter M.; Wood, Craig C.
Summary: Transgenic engineering of plants is important in both basic and applied research. However, the expression of a transgene can dwindle over time as the plant's small (s)RNA‐guided silencing pathways shut it down. The silencing pathways have evolved as antiviral defence mechanisms, and viruses have co‐evolved viral silencing‐suppressor proteins (VSPs) to block them. Therefore, VSPs have been routinely used alongside desired transgene constructs to enhance their expression in transient assays. However, constitutive, stable expression of a VSP in a plant usually causes pronounced developmental abnormalities, as their actions interfere with endogenous microRNA‐regulated processes, and has largely precluded the use of VSPs as an aid to stable transgene expression. In an attempt to avoid the deleterious effects but obtain the enhancing effect, a number of different VSPs were expressed exclusively in the seeds of Arabidopsis thaliana alongside a three‐step transgenic pathway for the synthesis of arachidonic acid (AA), an ω‐6 long chain polyunsaturated fatty acid. Results from independent transgenic events, maintained for four generations, showed that the VSP‐AA‐transformed plants were developmentally normal, apart from minor phenotypes at the cotyledon stage, and could produce 40% more AA than plants transformed with the AA transgene cassette alone. Intriguingly, a geminivirus VSP, V2, was constitutively expressed without causing developmental defects, as it acts on the siRNA amplification step that is not part of the miRNA pathway, and gave strong transgene enhancement. These results demonstrate that VSP expression can be used to protect and enhance stable transgene performance and has significant biotechnological application.